Frequency of Malignancy on Video-Assisted Thoracoscopic Pleural Biopsy in Patients with Exudative Pleural Effusion - Ullah, Farhan; Majeed , Farhan Ahmed; Umair, Bilal; Ullah, Muhib; Jawad; Farhan, Warda (Pakistan Armed Forces Medical Journal, 2024)
Objective: To identify the frequency of malignancy upon Video-assisted thoracoscopic pleural biopsy in patients with exudative pleural effusion. Study Design: Retrospective longitudinal study. Place and Duration of Study: Thoracic Surgery Department, CMH Rawalpindi, Pakistan from Jan 2022 to Aug 2023. Methodology: The study included 273 patients having exudative pleural effusion diagnosed upon pleural tap. Patients who had negative cytology and mycobacterial cultures were included in the study. The previous diagnostic procedures, histopathology, along with culture reports, were collected for all patients. Any additional procedures and complications of VATS were also documented in the patients. Results: Of 273 patients, 183(67.03%) male and 90(32.96%) females. VATS pleural biopsy revealed cancer in 81(29.67%) patients. Lung cancer was the most frequent malignancy, accounting for 49(17.94%) cases. Mesothelioma was found in 11(4.02%) cases, metastatic carcinoma in 21(7.69%) cases. 128(46.88%) were proven to have tuberculosis, non-specific inflammation was diagnosed in 64(23.44%) cases. VATS-related complications occurred in 34(12.45%) patients. No mortality was observed within 30 days of admission. Conclusion: The diagnosis of exudative pleural effusions can be safely and efficiently made by VATS pleural biopsy. The most prevalent diagnosis in our setup was pulmonary tuberculosis, followed by malignancies.